Children's mobile communicative practices and locational privacy. Issue 5 (19th August 2022) - Özkul, Didem
Abstract: Children start using smartphones increasingly from early ages. This makes it more difficult for them to develop an understanding of online privacy and managing their personal data. Many parents monitor and regulate children's online media use. However, they also encourage using smartphones to ensure the safety and security of their children. This study explores how children use smartphones in relation to their understanding of privacy of communication, content, data, and location. It examines data from 7 focus groups with arts-based methods conducted with 37 children in UK. The findings suggest that children think of their smartphones as a private communication technology and a private place, and they manage their locational privacy based on the necessity of using a mobile app and through adjusting the location settings on their phones. The findings also suggest that privacy of mobile data and user content are dependent on where mobile communication takes place. Lay Summary: This article presents the results of a study conducted with UK smartphones users who were 8- to 11-years old. The study had two aims. The first aim was to explore and understand the social and physical settings where children use their smartphones, and what kinds of communicative practices they engage with while using their smartphones. The second aim was to explore and analyze what children know about privacy in relation to where they use their smartphones and how they use them. The findings of the study suggest that children think of their smartphones and the content of their mobile communication as private. Their understanding of privacy can depend on the where they use their smartphone and what kinds of communication takes place on their smartphones. The findings also reveal that children who are 8- to 11-years old can value the peace of mind that their smartphones give to their parents more than their own locational privacy.